Third Progress Report on Inclusion of Enhanced Contractual Provisions in International Sovereign Bond Contracts. (Policy Papers; Policy Paper, 2017)
The IMF Executive Board endorsed in October 2014 the inclusion of key features of enhanced pari passu provisions and collective action clauses (CACs) in new international sovereign bonds.1 Specifically, the Executive Board endorsed the use of (i) a modified pari passu provision that explicitly excludes the obligation to effect ratable payments, and (ii) an enhanced CAC with a menu of voting procedures, including a 'single-limb' aggregated voting procedure that enables bonds to be restructured on the basis of a single vote across all affected instruments, a two-limb aggregated voting procedure, and a series-by-series voting procedure.2 Directors supported an active role for the IMF in promoting the inclusion of these clauses in international sovereign bonds.3 The IMFC and the G20 further called on the IMF to promote the use of such clauses and report on their inclusion. Since that time, the IMF has published periodic progress reports on inclusion of the enhanced clauses.4 These reports found that since the Executive Board's endorsement, substantial progress had been made in incorporating the enhanced clauses, with approximately 85 percent of new international sovereign bond issuances since October 2014 (in nominal principal amount) including such clauses. The reports also found that there was no observable market impact on inclusion of the enhanced clauses. However, the reports noted that the outstanding stock without the enhanced clauses remained significant, with issuers showing little appetite for liability management exercises to accelerate the turnover. This paper provides a further update on the inclusion of the enhanced clauses and on the outstanding stock of international sovereign bonds as of September 30, 2017. Section II reports on the inclusion of these enhanced provisions, finding that the vast majority of issuers are including these clauses, with only a few countries standing out against the market trend. Section II also provides an update on the outstanding stock, indicating that while the percentage of the outstanding stock with the enhanced clauses is increasing, a significant percentage of the stock still does not and little action has been taken by issuers to increase the rate of turnover. Section III briefly reports on the use of different bond structures, and Section IV describes the staff's ongoing outreach efforts and next steps.